Ganhos pedagógicos do trabalho com o gênero poema nos processos de alfabetização e letramento: uma proposta de ensino vivenciada no PIBID Pedagogia em Capanema-Pa. - NASCIMENTO, Wiltiana Maria Sousa do (2022)
This research describes and analyzes the results of a didactic sequence with the poem genre in a 4th grade elementary school class, in the context of the teaching initiation internship carried out in a public school in the city of Capanema-Pará. The general objective is to understand the contribution of the poem genre as a contextualized teaching tool of language practices (reading/listening, textual production, orality, linguistic and semiotic analysis) in the literacy and literacy processes. The investigation is anchored in the qualitative approach of scientific research, of a basic nature, with descriptive and explanatory purposes. The analyzes and discussions implemented were built based on the data collected by the author during her participation as a scholarship holder in the subproject Interdisciplinary Literacy and Literacy Practices in Elementary School, part of the Institutional Scholarship Program for Teaching Initiation (PIBID), carried out on the University Campus de Capanema from the Federal University of Pará (UFPA), in partnership with a public school in the municipal network, from August 2018 to January 2020. The research subjects are 26 students from the class accompanied by the intern author of the work during the internship activities and a class teacher. The technique used in the data collection was the participant observation, with the use of the field diary for the qualitative record of the facts that happened in the process of implementation of the didactic activities for the teaching of the aforementioned genre. Research data show that the advances achieved during the teaching experience were quite significant, given that students were able to successfully understand and develop the planned activities in all modules of the teaching plan. In this way, it is argued that the use of the poem genre as a pedagogical tool for literacy and literacy effectively collaborated with the students' learning, going beyond a mere mechanical and decontextualized reading and writing exercise. when the literary genre is worked in a contextualized and meaningful way, using various possibilities to develop literacy articulated with literacy, it ends up re-signifying the teaching of reading and writing at school and motivating students even more to learn.